Implicit modeling of abrasion process based on potential field. (May 2019) - Euzenat, Charly; Lavernhe, Sylvain; Tournier, Christophe
Abstract: This article presents a novel numerical model to generate abrasion surface topography. The main difficulty encountered regarding abrasion simulation is the numerical complexity caused by the number of interactions. In addition, the resulting surface topography is not only the result of cutting but also repelling and deforming matter. Thus the geometry is not strictly defined by the intersection between the grains and the mechanical part. Considering both numerical and physical constraints, an implicit geometrical model has been developed. The features of an implicitly defined surface make it a suitable candidate to address abrasion removal phenomenon. Within this formulation, the surface is embedded in a volumetric data set and is retrieved as the set of points having the same field value. Thus, the correlation between a scalar field and the specimen surface has been leveraged to model the abrasive grain actions. The removal action occurs throughout the penalization of the volumetric data field. The extension of each particle interaction range to model the plastic flow is done with negligible additional cost. Highlights: A new model based on implicit surfaces has been developed for abrasion simulation. The potential field takes into account material removal and repelling actions. The proposed model permits to reach high performances regarding computational time. The evolution of simulated surface roughness during process has been studied.